Evaluation Of Water Quality Of Karacalar Dam (Ulaş-Sivas) By Using Physico-Chemical Methods - Mutlu, Ekrem; Kutlu, Banu; Yanık, Telat; Demir, Tuğba (Journal of Selçuk University Natural and Applied Science - Digital Proceeding Of The ICOEST’2014 - , SIDE, 2014)
Located in Upper-Kızılırmak plateau, Karacalar Dam Lake is located within borders of Karacalar and Yapalı villages of Ulaş district of Sivas city, and the water resource of the barrage is Karacalar Brook. Karacalar Barrage Lake has 1353 m altitude, 4.40 km2 lake surface, 49 hm3 lake volume, and it is very important role in watering the agricultural lands of Ulaş district. In this study, it has been aimed to determine the water quality characteristics of Karacalar Barrage Lake (Ulaş- Sivas) via physico-chemical methods, and to determine its class according to Water Pollution and Control Regulation and Drinking Water Standards Regulation). This study has been started in March 2011, and it has lasted for 1 year. The water samples have been collected monthly from 3 stations representing the whole of the lake. Among the water quality parameters, dissolved oxygen (D.O.), saltiness, pH, temperature, electrical conductivity (E.C.), suspended solid matters (SSM), chemical oxygen demand (COD) biological oxygen demand (BOD), total alkalinity, total hardness, total ammoniac azote, nitrite, nitrate, phosphate, sulfate, sulfide, sodium, magnesium, calcium, ferrous, lead, copper and cadmium levels have been investigated in water samples. As a result of performed study, the monthly and seasonal water quality changes in Karacalar Barrage Lake has been determined, and it has been investigated it the lake is suitable for aquaculture activities.
Keywords: Water Quality, Karacalar Dam Lake, Ulaş, Sivas